2018
DOI: 10.1039/c8ob02056f
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i)-catalysed high-yielding synthesis of indenes by direct Csp3–H bond activation

Abstract: A catalytic, practical and high-yielding procedure for the synthesis of indenes by direct Csp3–H activation under gold(i) catalysis was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Nahide et al developed a gold (I)-catalyzed protocol for the synthesis of indenes 65 through direct CÀ H activation (Scheme 14). [19] For this strategy, variously substituted alkynyl triphenylmethanes 64 (starting materials) were prepared using Pd-catalyzed Sonogashira coupling. The only existing Csp 3 À H bond in the substrate was catalytically activated by gold (I) catalyst 66 (20 mol%) in DCE at 105°C.…”
Section: Gold-catalyzed Coupling Reaction Through Csp 3 à H Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nahide et al developed a gold (I)-catalyzed protocol for the synthesis of indenes 65 through direct CÀ H activation (Scheme 14). [19] For this strategy, variously substituted alkynyl triphenylmethanes 64 (starting materials) were prepared using Pd-catalyzed Sonogashira coupling. The only existing Csp 3 À H bond in the substrate was catalytically activated by gold (I) catalyst 66 (20 mol%) in DCE at 105°C.…”
Section: Gold-catalyzed Coupling Reaction Through Csp 3 à H Activationmentioning
confidence: 99%
“…Nahide et al . developed a gold (I)‐catalyzed protocol for the synthesis of indenes 65 through direct C−H activation (Scheme ) . For this strategy, variously substituted alkynyl triphenylmethanes 64 (starting materials) were prepared using Pd‐catalyzed Sonogashira coupling.…”
Section: Gold‐catalyzed Csp3−h Activation Processesmentioning
confidence: 99%
“…Gold is able to activate an alkyne group toward a nucleophilic addition and, for instance, make it susceptible to act as the receptor motif in a hydride shift reaction (Xie et al, 2014; Nahide et al, 2018). In this sense, Wong et al reported the gold-alkyne activation of 1,5-enynes 81 toward a rare 1,6-hydride shift leading to the gold-activated oxonium intermediate 90 , which then experiments a Prins-type cascade forming two new C—C bonds and furnishing the final tricyclic system 91 (Figure 9A) (Lu et al, 2018).…”
Section: Gold-catalyzed Isomerization Processes Involving An Initimentioning
confidence: 99%
“…The synthesis of indenes 71 was achieved under gold(I) catalysis by direct C sp3 –H activation of alkynyl triphenylmethanes 70 that proceeds via a pericyclic [1,5]‐H migration‐cyclization (Scheme ).…”
Section: Transition Metal (Tm)‐catalyzed Processesmentioning
confidence: 99%